Outpatient Use of Low Molecular Weight Heparin (Dalteparin) for the Treatment of Deep Vein Thrombosis of the Upper Extremity - Savage, K. J.; Wells, P. S.; Schulz, V.; Goudie, D.; Morrow, B.; Cruickshank, M.; Kovacs, M. J. (Thrombosis and Haemostasis, 1999)
Upper extremity deep vein thrombosis (DVT) is now recognized as a major cause of morbidity and mortality. There is little information regarding the most effective treatment of this condition. We report a prospective cohort study of the use of low molecular weight heparin (LMWH) in the outpatient management of upper extremity DVT. Forty-six patients were managed as outpatients for objectively documented upper extremity DVT with dalteparin (200 aXa u/kg), for a minimum of five days. Warfarin was usually initiated on the first day with a target INR of 2.0-3.0. Most patients had an underlying malignancy or a history of a central line. All patients were followed for 12 weeks from diagnosis. Only one patient had a major bleed. No patients developed pulmonary emboli. One patient had a recurrence of DVT during the treatment with LMWH with extension of the existing thrombus. Seven patients died, all due to their underlying disease. This study supports the safety and effectiveness of dalteparin in the treatment of upper extremity DVT. Given that these patients were treated as outpatients, there is a potential for huge cost savings.